Prevalence and severity of temporomandibular disorders among the orthodontic patients using fonseca's questionnaire - Sandhya Jain; Sunny Chourse; Deshraj Jain (Contemporary Clinical Dentistry, 2018)
Objective: The purpose of the study is to determine the prevalence of TMDs among the 12-18 years and 19-30 years patient age group requiring orthodontic treatment by using the Fonseca's questionnaire. Material and Methods: A total of 390 patients who visited the orthodontic department for treatment were asked to fill Fonseca's questionnaire. The results were analyzed for both the age groups and the percentage values were compared between males and females, different types of malocclusion and presence of TMDs. Results: In the 12-18 years age group, around 18.75% of the males and 12.28% of the females were having some degree of TMJ dysfunction. In the 19-30 years age group, around 30.32% of the females were found to have some severity of TMJ dysfunction as opposed to 19.23% of males. In the 12-18 years age group, around 11% of Class I, 16% of Class II and 50% of class III patients were having some degree of temporomandibular dysfunction. In the 19-30 years age group, the results showed that around 24% of Class I and class II patients and 50% of Class III patients presented with some degree of TMD. In the 12-18 years age group around 15% and in the 19-30 years age group, around 25% of the patients presented with some degree of TMD ranging from mild, moderate to severe. Conclusion: The study concludes that significantly more number of females presented with TMDs as compared to males in the 19-30 years age group. As the age increases the presence of TMDs also increases because of the significant presence of TMDs in the 19-30 years age group as compared to 12-18 years age group.